2000
DOI: 10.1046/j.1365-2958.2000.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase variation of a β‐1,3 galactosyltransferase involved in generation of the ganglioside GM1‐like lipo‐oligosaccharide of Campylobacter jejuni

Abstract: Ganglioside mimicry by Campylobacter jejuni lipo‐oligosaccharide (LOS) is thought to be a critical factor in the triggering of the Guillain–Barré and Miller–Fisher syndrome neuropathies after C. jejuni infection. The combination of a completed genome sequence and a ganglioside GM1‐like LOS structure makes C. jejuni NCTC 11168 a useful model strain for the identification and characterization of the genes involved in the biosynthesis of ganglioside‐mimicking LOS. Genome analysis identified a putative LOS biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
187
1
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(202 citation statements)
references
References 52 publications
10
187
1
4
Order By: Relevance
“…The gne (Cj1131c) gene of C. jejuni NCTC 11168 was initially annotated to encode a UDP-glucose 4-epimerase (GalE) based on functional characterization of its product (8,9). New evidence presented in this report conclusively demonstrates that gne encodes a bifunctional UDP-GlcNAc/Glc 4-epimerase.…”
Section: Discussionmentioning
confidence: 89%
“…The gne (Cj1131c) gene of C. jejuni NCTC 11168 was initially annotated to encode a UDP-glucose 4-epimerase (GalE) based on functional characterization of its product (8,9). New evidence presented in this report conclusively demonstrates that gne encodes a bifunctional UDP-GlcNAc/Glc 4-epimerase.…”
Section: Discussionmentioning
confidence: 89%
“…NIH-PA Author Manuscript NIH-PA Author Manuscript (7)(8)(9)(10). The genes coding for enzymes that synthesize these glycan moieties have been found in clusters throughout the C. jejuni genome.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Pseudaminic acid, the major modification of flagellin, is synthesized via the UDP-GlcNAc dehydratase PseB pathway (30,18). GalNAc, a major component in the biosynthesis of glycoprotein N-linked heptasaccharide, lipooligosaccharide (LOS), and capsule (7,8,10), is synthesized intracellularly by the C4 epimerase Gne (31). Table 3 lists the kinetic parameters of PseB and Gne derived from other studies, as well as GST-PglF from this study.…”
mentioning
confidence: 99%
“…Clearly, the identification of other genes involved in LOS synthesis and the study of their regulation are of considerable interest for a better understanding of the pathogenic mechanisms used by C. jejuni (24). In this regard, Linton et al (49) have reported that the wlaN gene product, which encodes a ␤-1,3-galactosyltransferase, is responsible for converting the GM2-like LOS structure to a GM1-like structure. The LPS of C. jejuni strain 81-176 expresses mainly a mixture of LPS cores containing GM2 and GM3 gangliosides (29).…”
Section: Genetic Variability Of Campylobacter Jejuni and Its Relationmentioning
confidence: 99%